Determination of Critical Periods of Soybean cv. Dema 2 Against Weeds in The Dry Season - Trisnaningsih, Umi; Firdausi, Annatasya Risqi; Suciaty, Tety (Ann Publisher, 2024)
Weed control by weeding is the safest alternative but requires a lot of labor and costs. Therefore, knowledge about the critical period for soybean plants against weeds is necessary so that weeding can be done timely and efficiently. This study aimed to determine the effect of weeding time on the growth and yield of soybean and critical period to weeds. The study was conducted in Mekarjaya Village, Gantar District, Indramayu Regency, from September to December 2023. The experimental design was Randomized Complete Block Design (RCBD). The treatments tested were the time of weeding which consisted of nine levels: weeds free, weeding at 3 weeks after planting (WAP), weeding at 4 WAP, weeding at 5 WAP, weeding at 6 WAP, weeding at 7 WAP, weeding at 8 WAP, B9 = not weeded. All treatments were repeated three time. The results showed that the time of weeding treatment had no significant effect on growth component but had a significant effect to yield components and yield of soybean. The time of weeding treatment showed that the critical period for soybean cultivar Dena 2 occurred at 0-9 WAP with a yield loss due to weed competition of 8.87% to 27%.